1985
DOI: 10.1159/000242182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Corticosteroids and Pancreatic Hormones on Carbamyl Phosphate Synthetase-I and Ornithine Transcarbamylase Activities in Fetal Rat Liver

Abstract: The effects of corticosteroids and pancreatic hormones on two mitochondrial enzymes of ureagenesis, carbamyl phosphate synthetase-I (CPS-I) and ornithine transcarbamylase (OTC), were investigated and compared in fetal rat liver. Supplementing hydrocortisone acetate (50 μg) to 18.5-day-old fetuses significantly increased CPS-I activity (by 36%) and decreased OTC activity (by 23%). An actinomycin D supply (2 μg) to 18.5-day-old fetuses prematurely increased OTC activity and decreased fetal insulin level (by 42%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1987
1987
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…Although most of the reports in the literature suggest an inhibitory effect of CS on OTC in fetal as well as in adult rats (Gautier et al 1985; Gautier et al 1977; Ulbright and Snodgrass, 1993), we observed a subtle and delayed up-regulation in this gene after both acute and chronic MPL. As has been mentioned in the previous section, the coordinated regulation of CS on CPS (the first enzyme of the ornithine cycle, converts ammonia, originating from amino acid degradation, into urea) or arginase (the last enzyme of the cycle) via CEBP-β could not be applied to the chronic data-set and thus these two genes were modeled independently of CEBP-β.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Although most of the reports in the literature suggest an inhibitory effect of CS on OTC in fetal as well as in adult rats (Gautier et al 1985; Gautier et al 1977; Ulbright and Snodgrass, 1993), we observed a subtle and delayed up-regulation in this gene after both acute and chronic MPL. As has been mentioned in the previous section, the coordinated regulation of CS on CPS (the first enzyme of the ornithine cycle, converts ammonia, originating from amino acid degradation, into urea) or arginase (the last enzyme of the cycle) via CEBP-β could not be applied to the chronic data-set and thus these two genes were modeled independently of CEBP-β.…”
Section: Discussioncontrasting
confidence: 83%
“…In this report, we investigated the dynamics of various genes related to the greater urea cycle, an important biochemical pathway present in mammalian livers for nitrogen disposal. Many of these enzymes are known to be highly regulated by CS in the liver (Christowitz et al 1981; de Groot et al 1984; Gautier et al 1985). …”
Section: Discussionmentioning
confidence: 99%
“…With respect to ASS activity, combination of these two compounds always gave synergistic responses. These results Dexamethasone 0.751 50.063 (4) 78.7k 10.9 (6) 0.884k0.056 (5) 0.313f0.041 (6) 181.9i20.9 (7) Glucagon + 0.636k0.071 (5) 87.5 10.6 (5) 0.686i0.100 (5) 0.350i0.040 ( 5 ) 348.2i32.0 (5) actinomycin D Dexamethasone + 0.491 f 0.057 (4) 83.6k 12.7 ( 5 ) 0.699 f 0.080 (5) 0.200 f 0.038 (5) 99.0f 8.3 (7) Hepatocytes from 18.5-day-old foetuses were cultured for 24 h in control medium before the compounds were added. Cells were harvested 24 h after the addition of the different compounds (lo-' M glucagon; A4 dexamethasone; 0.2 pg/ml actinomycin D ; 1 pg/ml cycloheximide).…”
Section: Discussionmentioning
confidence: 71%
“…Ornithine carbamoyltransferase was a cluster 6 gene with dual regulation by CS and captured by model D. Rats receiving 50 g of hydrocortisone i.p. injection showed ornithine carbamoyltransferase suppression, and 50-g dibutyryl-cAMP administration could induce this enzyme (Gautier et al, 1985). Therefore, CS-induced cAMP may act as BS a causing the delayed induction.…”
Section: Modeling Of Corticosteroid Pharmacogenomics 105mentioning
confidence: 88%